CONCEPTUAL MODEL OF ENTERPRISE DIGITAL TRANSFORMATION MANAGEMENT FOR ENSURING SUSTAINABLE REGIONAL DEVELOPMENT - Костянтин Завражний; Ірина Сотник; Анжеліка Кулик (Економіка та суспільство)
This article explores the potential of enterprise digital transformation as a tool for inclusive and sustainable regional development in Ukraine amidst multiple overlapping crises caused by war, socio-economic inequality, environmental challenges, and technological divides. The study begins with a critical analysis of existing digitalization approaches, which, while primarily focused on large corporations, tend to overlook environmental, social, and regional dimensions, as well as the specific needs of small and medium-sized enterprises as key agents in local economies. The main objective of this research is to conceptualize digital transformation within the context of regional SMEs and develop an integrated management model that, unlike existing frameworks, addresses the challenges of post-war recovery while aligning digitalization strategies with sustainable development principles. The study substantiates the necessity of transitioning from fragmented digital initiatives toward a comprehensive approach that combines strategic vision, organizational adaptability, resource availability, process agility, and a culture of innovation. This approach integrates ecological and social priorities into the digital transformation framework, while also reflecting the specificities of a post-crisis economy. Special emphasis is placed on identifying and analyzing the barriers that hinder sustainable digital transformation among regional SMEs. Based on empirical and secondary data, the study identifies critical challenges including limited access to finance, a shortage of digital and «green» skills, resistance to change, lack of institutional support, and underdeveloped digital infrastructure in certain regions. The article highlights the growing digital divide as a key factor exacerbating regional disparities and undermining the inclusivity of the recovery process. These barriers are recognized as interconnected and require coordinated, cross-sectoral responses from government, businesses, academia, and international partners. The practical value of the proposed model lies in its potential to serve as a roadmap for SMEs aiming to implement sustainable digital transformation, as well as a foundation for designing public support policies and guiding international donor programs. The successful realization of digital transformation’s potential calls for coordinated efforts across all stakeholders, including the state, business sector, academic institutions, and civil society. Priority areas for implementation include expanding digital infrastructure, enhancing digital competencies, addressing institutional gaps, and creating an enabling regulatory environment. This research offers a holistic perspective on sustainable digital transformation as a multidisciplinary and multilevel process that merges innovation with the principles of equity, resilience, and equal access. The proposed approaches and findings hold practical relevance for achieving sustainable, inclusive, and regionally balanced development.